2016
DOI: 10.1063/1.4965294
|View full text |Cite|
|
Sign up to set email alerts
|

Resilience of thermal conductance in defected graphene, silicene, and boron nitride nanoribbons

Abstract: Nanomaterials hold great promise for applications in thermal management and thermoelectric power generation. Defects are important as they can be either inevitably present during fabrication or intentionally introduced to engineer properties. Here, we investigate how thermal conductance responds to edge defects in narrow graphene, silicene, and boron nitride nanoribbons (NRs), from first principles using non-equilibrium Green's function method. Geometric distortions, phonon conductance coefficients, and local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Given their buckled atomic structure, [14] silicene nanoribbons (SNRs) have a nonzero energy gap, which can be tuned further by applying external transverse electric fields and doping. [15] A few strategies have also been used to reduce thermal transport in SNRs, including adding substrates, [16,17] surface functionalization, [18] defect, [11,19,20] and strain. [21] These studies provide significant guidance for experimental realization.…”
Section: Introductionmentioning
confidence: 99%
“…Given their buckled atomic structure, [14] silicene nanoribbons (SNRs) have a nonzero energy gap, which can be tuned further by applying external transverse electric fields and doping. [15] A few strategies have also been used to reduce thermal transport in SNRs, including adding substrates, [16,17] surface functionalization, [18] defect, [11,19,20] and strain. [21] These studies provide significant guidance for experimental realization.…”
Section: Introductionmentioning
confidence: 99%
“…This shift would also change the chemical potential that maximizes ZT . On the other hand, edge disorder is known to decrease phonon-contributed thermal conductance, so potential trade-offs between this effect and any induced electron–phonon scattering would need to be analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…For each system, we have Gaussian write molecular orbital coefficients and corresponding eigenvalues, which give us the Hamiltonian eigenvalues and eigenvectors. These, along with overlap and force constant matrices, are obtained following optimization and input into our program TARABORD that calculates electron and phonon transmission coefficients ( T e and T p , respectively) as functions of energy, using the ab initio based nonequilibrium Green’s function (NEGF) method. The method mathematically constructs an infinite open system with a junction consisting of one unit cell and semi-infinite contact nanoribbons consisting of periodically repeated structures to the left and right.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These defects not only significantly affect the electronic properties of the material, but also act as phonon localization/delocalization centers, with the consequent deterioration of the thermal properties. 34,52,53 By using firstprinciples calculation, several authors have studied different configurations of defects in silicene, considering single vacancies, groups of vacancies (clusters), or even extended line of defects. 54,55 In these works, it is shown that due to silicene presents sp 3 hybridization, the formation energy of these defects is reduced, and consequently, the defective silicene becomes a stable structure.…”
Section: A Impact Of Vacancies On the Thermal Conductancementioning
confidence: 99%